2005
DOI: 10.1016/j.trstmh.2004.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Identification of three members of the Anopheles funestus (Diptera: Culicidae) group and their role in malaria transmission in two ecological zones in Nigeria

Abstract: The role of the Anopheles funestus group in malaria transmission was investigated in two ecological zones in Nigeria. Sampling was carried out at four sites each around Ibadan (forest) and Ilorin (savanna). Human landing catches were supplemented with indoor and outdoor resting collections. PCR was used to identify 1848 A. funestus group mosquitoes to species level (749 in the savanna, 1099 in the forest) and three species were identified. In the forest, A. funestus s.s. predominated (55.4%), followed by A. ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
48
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 13 publications
6
48
0
Order By: Relevance
“…There are seven ecological zones in Nigeria, the arid savannah in the north gradually turning to humid forest in the south. 10 Rainfall is the real climatic variable in Nigeria with June to September the rainiest months throughout the country. Mosquitoes were collected from the following four ecotypes based on accessibility, logistics, personnel and ethical reasons.…”
Section: Study Areasmentioning
confidence: 99%
“…There are seven ecological zones in Nigeria, the arid savannah in the north gradually turning to humid forest in the south. 10 Rainfall is the real climatic variable in Nigeria with June to September the rainiest months throughout the country. Mosquitoes were collected from the following four ecotypes based on accessibility, logistics, personnel and ethical reasons.…”
Section: Study Areasmentioning
confidence: 99%
“…Awolola et al [8] reported that there is little information on sporozoite rates of Anopheles mosquitoes. This observation was the basis of several studies he carried out in Nigeria from 2003 -2005.…”
Section: Malaria Parasitesmentioning
confidence: 99%
“…Meanwhile, the distribution of the molecular M (Mopti) and S (Savannah) forms of An. gambiae s.s is still being determined for much of the West African regions [6,8]. The malaria problem in sub-Saharan Africa represents a peculiar case because the vectoral system is the most complex anywhere.…”
Section: Malaria Parasitesmentioning
confidence: 99%
See 2 more Smart Citations